EMERGENCY TREATMENT OF SVT: ADENOSINE VERSUS VERAPAMIL - Naeem Asghar; Shakeel Ahmad; Awais-ur-rehman (Journal of University Medical & Dental College, 2017)
ABSTRACT: Introduction: Supraventricular tachycardia (SVT) is a common arrhythmia seen in critical care settings. After vagal maneuvers, adenosine 6 to 12 mg intravenous bolus is the initial drug of choice. Intravenous Verapamil, 5 to 10 mg can terminate SVT if vagal maneuvers and adenosine are ineffective. Objective: Comparison of efficacy of adenosine versus verapamil in the emergency treatment of SVT. Study Design: Randomised control trial. Setting: Emergency department. Duration of Study: 6 months. Subjects: A total number of 210 patients presenting in emergency department with the diagnosis of PSVT on ECG. Methods: Patients divided into two groups. Group A patients were given adenosine. If SVT persisted then the patient were shifted to verapamil group. Group B patients were given intravenous verapamil. If SVT persisted then the patient were shifted to adenosine group. Patients were monitored for next 30 minutes. Results: In Group A, 63 (60%) patients were converted to sinus rhythm with 6 mg bolus. 20 (19.04%) patients converted to sinus rhythm with an additional 12 mg adenosine. Efficacy of adenosine was 79.0%. In Group B, treated with verapamil, 86 (81.90%) patients converted to sinus rhythm with 5 mg dose. 9 (8.57%) patients converted to sinus rhythm with an additional 5 mg verapamil. Efficacy of verapamil was 90.5%. The mean dose of the drug used was 5.89 mg S.D + 1.92. Overall, efficacy of verapamil (90.5%) was statistically greater than adenosine (79.0%), p value of 0.021. Conclusion: Verapamil was more effective than adenosine in the emergency treatment of PSVT.